Aplikasi Inventaris Berbasis Website Pada Toko Naomi Wig Menggunakan Metode Extreme Programing - Dylen, Varel; Lee, Francka Sakti; Geasela, Yemima Monica (Prodi Sistem Informasi Universitas Dharma Andalas, 2024)
Naomi Wig store is a commercial company that sells of wigs and hair accessories. In the activity of recording and managing the inventory of Naomi Wig store, the author found several problems that were caused by error or inaccuracy in recording or selling the inventory. The reason is mostly inventory management, which still uses manual methods in the form of paper records which are prone to loss or damage. The next most common cause is the failure to record in-stock and out-of-stock items in the Naomi Wig store. To reduce the occurrence of these problems, the authors propose to create a web-based inventory application for the Naomi Wig Store. This study used the Extreme Programming Method as its methodology. As a result of this research, an inventory application was created with several important functions to manage the entry and exit of goods from the Naomi Wig Store, such as the collection of data on purchases, sales, inventory lists, and item return lists. This study’s conclusion is that by using a web-based inventory application in the Naomi Wig store can facilitate the management of incoming and outgoing data of Naomi Wig store.